PENGARUH INKLUSI KEUANGAN DAN HUMAN CAPITAL TERHADAP PRODUKSI USAHA TANI BUNGA POTONG - Ayuningtyas, Nia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Floriculture has become a featured agricultural business of Batu city, thanks to people’s high demand for aesthetic cut flowers. As the commodity can be harvested faster and can be used for various occasions, this business is very potential for further development. The objective of this research is to identify the effects of financial inclusion and human capital on the production of floriculture in Gunungsari village of Bumiaji sub-district in Batu city. The data of this quantitative research war harvested from questionnaires distributed to 160 respondents. Here Cobb-Douglas production function was used in the multiple linear regression to identify the elasticity of the independent variables on the dependent variable and the return to scale of the agricultural business. This study finds that financial inclusion, which is perceived from access to banking credits and loans, and human capital, which is observed from education level, significantly influence the production of cut flowers. Further, the return to scale of floriculture is categorized into increasing return to scale. The implications of the research are that the agricultural businesspeople need to be incorporated into the financial inclusion and that improvements are required in the quality of education regarding agriculture so that the entrepreneurs can allocate resources efficiently to optimize their production. Keywords: cut flower; financial inclusion; human capital